Rapid amyloid‐β oligomer and protofibril accumulation in traumatic brain injury. (19th June 2017) - Abu Hamdeh, Sami; Waara, Erik Rollman; Möller, Christer; Söderberg, Linda; Basun, Hans; Alafuzoff, Irina; Hillered, Lars; Lannfelt, Lars; Ingelsson, Martin; Marklund, Niklas
Abstract: Deposition of amyloid‐β (Aβ) is central to Alzheimer's disease (AD) pathogenesis and associated with progressive neurodegeneration in traumatic brain injury (TBI). We analyzed predisposing factors for Aβ deposition including monomeric Aβ40, Aβ42 and Aβ oligomers/protofibrils, Aβ species with pronounced neurotoxic properties, following human TBI. Highly selective ELISAs were used to analyze N‐terminally intact and truncated Aβ40 and Aβ42, as well as Aβ oligomers/protofibrils, in human brain tissue, surgically resected from severe TBI patients ( n = 12; mean age 49.5 ± 19 years) due to life‐threatening brain swelling/hemorrhage within one week post‐injury. The TBI tissues were compared to post‐mortem AD brains ( n = 5), to post‐mortem tissue of neurologically intact (NI) subjects ( n = 4) and to cortical biopsies obtained at surgery for idiopathic normal pressure hydrocephalus patients (iNPH; n = 4). The levels of Aβ40 and Aβ42 were not elevated by TBI. The levels of Aβ oligomers/protofibrils in TBI were similar to those in the significantly older AD patients and increased compared to NI and iNPH controls ( P < 0.05). Moreover, TBI patients carrying the AD risk genotype Apolipoprotein E epsilon3/4 (APOE ε 3/4; n = 4) had increased levels of Aβ oligomers/protofibrils ( P < 0.05) and of both N‐terminally intact and truncated Aβ42 ( P < 0.05) compared to APOE ε 3/4‐negative TBI patients ( n = 8). Neuropathological analysis showed insoluble Aβ aggregates (commonly referred to as Aβ plaques) in three TBI patients, all of whom were APOE ε 3/4 carriers. We conclude that soluble intermediary Aβ aggregates form rapidly after TBI, especially among APOE ε 3/4 carriers. Further research is needed to determine whether these aggregates aggravate the clinical short‐ and long‐term outcome in TBI.